Transforming Traditions: Exploring the Adaptation of Nganteuran Tradition during the COVID-19 Pandemic - Hidayah, Irma Mulya (UIN Sunan Gunung Djati Bandung, 2023)
This study examines the changes in the Nganteuran tradition during the COVID-19 pandemic in Cianjur Regency. Using a qualitative approach, in-depth interviews were conducted with purposively selected participants. The findings reveal a decline in community participation in the tradition due to physical limitations and concerns about virus transmission. Instead of physical visits, individuals opted for exchanging greetings through text messages or phone calls. Adjustments were made in the execution of the tradition, including reducing the number of visited houses, prioritizing visits to immediate family members, or organizing virtual Nganteuran events via video conferencing platforms. The pandemic also influenced the perception and attitudes of the community, with emerging concerns and caution in participating. However, despite the challenges, the Nganteuran tradition persisted with adaptations made by the community. This research provides insights into how local traditions adapt to unforeseen changes, emphasizing the importance of reconfiguring social relationships in the context of a pandemic.